HYBRID SOLAR INVERTERS: A COMPREHENSIVE REVIEW (International Journal of Engineering Management Science, 2024)
It investigates hybrid solar inverters, providing a thorough analysis of their features, benefits, applications, difficulties, and potential future developments. Hybrid solar inverters, a key component of sustainable energy solutions, combine solar panels and energy storage systems, displaying intricate technological details that maximize DC to AC conversion. Case studies from real-world implementations demonstrate how well they work to achieve both off-grid and grid-tied functionality while fostering energy independence. Notwithstanding significant benefits, drawbacks like financial consequences, upkeep needs, and compatibility problems are discussed to provide a fair picture. Successful case studies and a variety of applications, from industrial to domestic, demonstrate how versatile crossbreed solar inverters are in real-world situations. The article anticipates breakthroughs in energy storage, smart grid integration, and artificial intelligence integration for improved performance, and it looks ahead to future developments in these areas. It also emphasizes how important hybrid solar inverters are to the development of renewable energy systems. They are in a position to play a significant role in the continuing worldwide shift toward a cleaner and more resilient energy infrastructure because of their potential benefits to sustainability and energy efficiency.
Keywords: Hybrid solar inverters, Renewable energy, Sustainable energy solutions, Energy management, Energy storage systems, Grid-tied functionality, Off-grid functionality, Energy independence